2023
DOI: 10.1002/jbm.b.35234
|View full text |Cite
|
Sign up to set email alerts
|

The influences of PEG‐functionalized graphdiyne on cell growth and osteogenic differentiation of bone marrow mesenchymal stem cells

Abstract: Guided bone regeneration (GBR) is a frequently used technique for patients with insufficient alveolar bone. The discovery of bone substitutes that can enhance osteogenesis is critical for GBR. Graphdiyne (GDY), a newly discovered carbon-based nanomaterial, has been recognized as the most stable allotrope of acetylene carbon and is anticipated to be able to promote osteogenesis. Whereas it still remains unknown whether it could enhance osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Current Results: Initial studies have demonstrated the biocompatibility and potential of graphdiyne scaffolds for promoting tissue regeneration in bone [132], nerve [133], and cardiac tissues [134]. Graphdiyne's ability to support cell growth and facilitate tissue repair offers promising opportunities in regenerative medicine [135].…”
Section: Graphdiyne In Tissue Engineering and Biomedical Devicesmentioning
confidence: 99%
“…Current Results: Initial studies have demonstrated the biocompatibility and potential of graphdiyne scaffolds for promoting tissue regeneration in bone [132], nerve [133], and cardiac tissues [134]. Graphdiyne's ability to support cell growth and facilitate tissue repair offers promising opportunities in regenerative medicine [135].…”
Section: Graphdiyne In Tissue Engineering and Biomedical Devicesmentioning
confidence: 99%
“…Stem cells possess anti-inflammatory properties, encourage the proliferation of epithelial cells, and hinder wound scarring [ 2 ]. Moreover, both stem cells and their exosomes exert notable impacts on the regeneration of bone tissue and the nervous system [ 3 , 4 ]. Different cell types with stem cell properties have been derived and characterized from different dental/oral tissues, making the teeth and the supporting oral tissues attractive and accessible sources of stem cells [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells have anti‐inflammatory properties, promote epithelial cell proliferation, and inhibit wound scarring 10,11 . In addition, stem cells and their exosomes have significant effects on bone tissue and nervous system regeneration 12,13 . Therefore, researchers have envisioned the application of stem cells in regenerative medicine to promote skin and bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 In addition, stem cells and their exosomes have significant effects on bone tissue and nervous system regeneration. 12 , 13 Therefore, researchers have envisioned the application of stem cells in regenerative medicine to promote skin and bone tissue regeneration. However, due to the difficulties of stem cell transportation and preservation, as well as their tumorigenicity and the difficulty of exosome extraction, nanoformulations of stem cells have been studied and have gradually become a hot research topic for elucidating new ways to repair damaged skin and bone.…”
Section: Introductionmentioning
confidence: 99%